The Concept of the Ba Baluak Tando Tradition as Strengthening the Marriage Agreement in Customary Law in Nagari Kurai V Jorong - Reza, Fadly; Irianto, Kartika Dewi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The ba baluak tando tradition is a very important procession in the proposal in the Kurai V Jorong indigenous community, in Bukittinggi City. This tradition not only functions as a social aspect, but also has customary legal meanings related to the concept of agreement in the process leading up to marriage. This study was made by the researcher to analyse the ba baluak tando tradition, its implementation process, and its relevance to customary law agreements, civil law, and the Supreme Court's jurisprudence on the voidness of agreements. The research used a juridical sociological approach by interviewing customary leaders to gain a deeper understanding of this tradition. Not only that, researchers also cite, journals, traditional books, and include verses of the Koran as sharia law according to the Minangkabau customary philosophy is Adat Basandi Syarak, Syarak Basandi Khitabullah. This research can provide an understanding of the conception of the ba baluak tando tradition as a strengthening of the marriage agreement in customary law in Nagari Kurai V Jorong.